Synthetically Tuned Pd-Based Intermetallic Compounds and their Structural Influence on the O2 Dissociation in Benzylamine Oxidation - Marakatti, Vijaykumar S; Sarma, Saurav Ch; Sarkar, Shreya; Krajčí, M; Gaigneaux, Eric M; Peter, Sebastian C (ACS applied materials & interfaces, 2019)
Intermetallic compounds (IMCs) have diverse electronic and geometrical properties to offer. However, the synthesis of intermetallic nanoparticles is not always easy; developing new methodologies that are conventional for many systems can be challenging, especially when incorporating highly electropositive metals to reduce to IMCs using solution synthesis methodologies. In this study, we report a comprehensive approach to access nanocrystalline PdxMy (M = Cu, Zn, Ga, Ge, Sn, Pb, Cd, In) intermetallic (IM) via the coreduction method employing sodium borohydride as the reductant. A combination of diffraction, spectroscopic, and microscopic techniques were performed to characterize the formed nanoparticles in terms of their phase composition, purity, particle size distribution, and surface oxidation properties of metals, respectively. IMCs of Pd with the elements such as Cu, Zn, Ga, and Ge exhibited higher catalytic activity that with elements such as In, Sn, Pb, and Cd. The DFT studies on these compounds revealed that the adsorption of benzylamine at the Pd site and the dissociative adsorption of O2 on the IM surface play a significant effect on catalytic activity. Among them, PdCu IM exhibited an excellent conversion of benzylamine (94.0%), with 92.2% of dibenzylimine selectivity compared to other IMCs. Moreover, PdCu exhibited decent recyclability and activity for the oxidation of different substituted primary amines.Intermetallic compounds (IMCs) have diverse electronic and geometrical properties to offer. However, the synthesis of intermetallic nanoparticles is not always easy; developing new methodologies that are conventional for many systems can be challenging, especially when incorporating highly electropositive metals to reduce to IMCs using solution synthesis methodologies. In this study, we report a comprehensive approach to access nanocrystalline PdxMy (M = Cu, Zn, Ga, Ge, Sn, Pb, Cd, In) intermetallic (IM) via the coreduction method employing sodium borohydride as the reductant. A combination of diffraction, spectroscopic, and microscopic techniques were performed to characterize the formed nanoparticles in terms of their phase composition, purity, particle size distribution, and surface oxidation properties of metals, respectively. IMCs of Pd with the elements such as Cu, Zn, Ga, and Ge exhibited higher catalytic activity that with elements such as In, Sn, Pb, and Cd. The DFT studies on these compounds revealed that the adsorption of benzylamine at the Pd site and the dissociative adsorption of O2 on the IM surface play a significant effect on catalytic activity. Among them, PdCu IM exhibited an excellent conversion of benzylamine (94.0%), with 92.2% of dibenzylimine selectivity compared to other IMCs. Moreover, PdCu exhibited decent recyclability and activity for the oxidation of different substituted primary amines.